ENGLISH FOR OCCUPATIONAL PURPOSES (EOP): ENHANCING COMMUNICATION SKILLS FOR MAGISTER ACCOUNTING STUDENTS UNPAM - Sumartini, Tutut (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Most professionals are aware now what are happening globally and are involved in using English, which is as a tool for communication in their job settings. In the context of English for Occupational Purposes (EOP) course, to be professional and productive in their job, having very good job both in English competence and performance is a must through preparing students with their right and materials in their study program. In this paper, the researcher deals with magister accounting students of UNPAM. This group of language learners needs to work and practice a lot with specific materials related to the student’s real lives used. English for communication that can lead them to be professional in their job settings.